RTID-05. THE MULTI-ARM GLIOBLASTOMA AUSTRALASIA (MAGMA) TRIAL. (12th November 2021) - Kong, Benjamin; Sim, Hao-Wen; Koh, Eng-Siew; Gan, Hui; Barnes, Elizabeth H; Yip, Sonia; Nowak, Anna K; Lau, Peter; Cuff, Katharine; Khoo, Eric; Lwin, Zarnie; Cooper, Adam; et al.
Abstract: BACKGROUND: Survival outcomes for patients with newly diagnosed glioblastoma have not changed significantly since the introduction of concurrent temozolomide with post-surgical radiation followed by adjuvant temozolomide. METHODS: Multi-Arm Glioblastoma Australasia (MAGMA) is a recently initiated phase III multi-arm, multi-centre randomized trial for patients with newly diagnosed glioblastoma, led by the Australian Cooperative Trials Group for Neuro-Oncology (COGNO), that will concurrently test multiple treatment questions. Initially, a partial factorial design will be implemented to compare the current standard of care with either or both of (1) neoadjuvant temozolomide and (2) aduvant temozolomide continued beyond six months until progression. MAGMA will transition to a multi-arm multi-stage (MAMS) design as additional tratment question are introduced. Treatment allocation to each question will be balanced (1:1) using minimisation over several stratification factors, including study site, age, IDH -mutation status, surgical extent and randomization to the prior treatment question(s). The primary outcome is overall survival. Secondary outcomes include progression-free survival (measured by mRANO), time to first non-temozolomide systemic treatment, clinically significant toxicity as measured by Grade 2/4 adverse events, and health-related quality of life measures. Parsimonious data collection and a streamlined assessment schedule have been incorporated to mitigate the burden of data collection (such as low grade toxicity from temozolomide), and to encourage participation in regional and rural settings. A consortium model has been adopted to foster neuro-oncology expertise and infrastructure and share academic credit and future design opportunities. PROGRESS: Recruitment commenced in September 2020. To date, 60 patients have been recruited from an initial sample size target of 250 patients for each of these initial two treatment questions. Of these 60 patients, 45 have been randomized in Question 1 (neoadjuvant chemotherapy) whilst 50 randomized in Question 2 (prolonged adjuvant chemotherapy). To date, 14 of the 27 intended sites are open to recruitment.